An integrated full consistent LOPCOW-EDAS framework for modelling consumer decision making for organic food selection - Sanyal Aparajita; Biswas Sanjib; Sur Samiran (Yugoslav Journal of Operations Research)
Over the years, there has been an upsurge in the buying and consuming green products like organic foods. However, past studies are limited to exploring the effects of behavioral factors on consumers' buying decisions for green products. The present paper fills the gap in the literature by providing a multi-criteria decision-making (MCDM) framework for consumer decision-making for selecting organic foods. To set the criteria for comparing organic foods, the theoretical foundation of the consumers’ black box model concerning the intention-behavior gap is applied. The present paper proposes an intuitionistic fuzzy number (IFN) based hybrid Logarithmic Percentage Change-driven Objective Weighting (LOPCOW) and Evaluation based on Distance from Average Solution (EDAS) model with an inherent capability to check the consistency in the calculation of the criteria weights with the help of the Full Consistency Method (FUCOM). The results have shown that greenwashing has changed the customers' mindset and they are considering mostly the factors of organic food selection that are the same as traditional products in the market. The output has provided a valid, robust and reliable solution, further established by performing sensitivity analysis.